FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PETANI KARET YANG DIKELOLA OLEH PTPN XII (PERSERO) - Sari, Rini Kartika; Tulhusnah, Lusiana (Relawan Jurnal Indonesia, 2024)
This study aims to determine the influence both simultaneously and partially between the variables of Labor, Land Area, Fertilizer, Capital and Wages on Rubber Production results and to determine the most dominant influence between the variables of Labor, Land Area, Fertilizer, Capital and Wages on Rubber Production results. The data collection method in this study is the primary and secondary methods. Where for data analysis using Multiple Regression Method, F Test and t Test. Based on the analysis that has been done, it can be concluded that first, simultaneously (together) it is known that the Fcount value> Ftable means Ho is rejected and accepts Ha which means there is a simultaneous influence between the variables of Labor, Land Area, Fertilizer, Capital and Wages on Rubber Production results. Second, partially it is known that Labor (X1) and Wages (X5) both have a t count value> t table which means there is a partial influence on Rubber Production. While the variables of Land Area (X2), Fertilizer (X3) and Capital (X4) all have the same tcount value < ttable which means there is no partial influence on Rubber Production. And third, the dominant Labor variable. This can be seen from the multiple linear regression coefficient figures for Labor (X1) of 0.399; Land Area (X2) of 0.171; Fertilizer (X3) of -0.004; Capital (X4) of 0.061 and Wages (X5) of 0.353.